Methods Used to Identify, Test, and Assess Impact on Preferences of Bolt-Ons: A Systematic Review - Geraerds, Alexandra J.L.M.; Bonsel, Gouke J.; Janssen, Mathieu F.; Finch, Aureliano Paolo; Polinder, Suzanne; Haagsma, Juanita A. (Value in health, 2021)
The question of whether additional dimensions should be added to the EQ-5D, so-called bolt-ons, has been researched since the 1990s. Several candidate bolt-ons have been tested. The aim of this systematic review was to provide an overview of EQ-5D bolt-on studies, including the origin of possible suitable bolt-ons, their format, and methods that were used to examine their value. Studies were identified through database search and reference screening and assessed based on a set of inclusion criteria. All studies that investigated bolt-ons for the EQ-5D were eligible for inclusion. Two reviewers independently extracted information from all included studies on objectives, study design, EQ-5D version used, the investigated bolt-ons, methods used to achieve objectives, and outcomes. Of 308 initially identified studies, 28 studies met the inclusion criteria. Of these studies, 3 identified potentially suitable bolt-on dimensions, 13 investigated the psychometric performance of EQ-5D + bolt-on(s), and 6 investigated the impact of the bolt-on on health state preferences. In total, 26 bolt-ons were identified, of which cognition was the most frequently mentioned. A wide variety of bolt-on identification methods, psychometric performance tests, and health state valuation methods were used in the included studies. A range of bolt-on dimensions has been investigated using diverse methods. Guidelines are needed to standardize the wording of the bolt-on dimension and response options, evaluate minimal important gain of the bolt-on, and facilitate quality assessment of bolt-on studies. Subsequently, guidelines will facilitate decision making on whether or not to implement a bolt-on dimension to the EQ-5D. •Previous studies on the EQ-5D reported psychometric shortcomings in particular populations. Multiple studies have identified and tested so-called bolt-on(s), additional dimensions for the EQ-5D that aim to improve the accuracy and precision of the EQ-5D. However, an overview of all bolt-on studies and all methods that were used to identify and test bolt-on dimensions is lacking.•This systematic review provides an overview of EQ-5D bolt-on studies, including the origin of possible suitable bolt-ons, their format, and methods that were used to examine their value. In addition, a new quality checklist was developed to determine quality of bolt-on studies.•This research offers an overview of all bolt-ons studies that have been conducted so far, and the methods that were used for identification, testing of psychometric performance, and assessing impact on health state preferences. This overview can help to create guidelines on how to conduct a bolt-on study, to enable decision making on whether or not to include a bolt-on in the EQ-5D.